Melahirkan Nyaman dan Cepat dengan Hypnobirthing - Widiawati, Ida (Universitas Tribhuwana Tunggadewi, 2019)
Duration of the active phase, first stage is 301, 67 minutes (5 hours), prolonged labor if labor lasts more than 24 hours or cervical dilatation is on the alert line of active labor (partograph) and unborn baby. The results found that hypnobirthing was significantly associated with the average length of labor in the hypnosis group (mean difference -165.20, 95% CI -223.53 to 106.87). The main objective of this study was to analisys correlation of hypnobirting with the duration of labour of the active phase, first stage. This study was a quasi-experimental research with post test only with control design and data analysis using independent t test. Result : The mean ± SD length of the active-phase, first stage was shorter (146  60 minute) among intervention grup than that of control grup (265 minuts  90 minute ). Hypnobirthing had significant correlation with duration of labour (P value 0,000= P< 0.05). Hypnobirthing can be used as a complementary therapy to increase comfort and duration of labor.